Rectal inclusion cyst as a complication of stapled hemorrhoidopexy: A case report. Issue 22 (June 2018) - Liu, Liancheng; Zhang, Yuru; Duan, Hongyan; Su, Yue; Xiong, Fang; Jia, Shan
Abstract: Rationale: Stapled hemorrhoidopexy is gaining popularity for prolapsing hemorrhoids. However, like any other operation, there is always the potential risk of complications. Rectal inclusion cysts are rare complications that results from the potential space in the staple line. Patient concerns: A 49-year-old woman was admitted to our hospital with a complaint of anorectal pain and fever complaints after stapled hemorrhoidopexy. The endoanal ultrasonography showed unclear fluid containing a cystic lesion circuit to the rectum at the staple line. Diagnoses: The endoanal ultrasonography strongly indicates the rectal inclusion cysts. Interventions and outcomes: A full thickness excision of the cyst was carried out along the staple line. The patient had complete recovery, with no recurrence or complaints for at least 6 months after the surgery. Lessons: Endosonography has an important role in investigating symptomatic patients after stapled hemorrhoidopexy. Once an inclusion cyst is diagnosed, excision of the stapled line is the only choice of treatment.